PHYSICAL AND CHEMICAL CHARACTERISTICS OF MANGROVE BAKAU KACANG FRUIT FLOUR (Rhizophora apiculata) - Oktaf Rina; Septian Cahaya Ramadhan; Erdi Suroso; Susilawati (Journal of Innovation Research and Knowledge, 2026)
Rhizophora apiculata mangrove fruit can be processed into food products and to maintain its shelf life it is processed into flour. Currently there are not many studies that examine the properties, content, and benefits of it. Therefore, testing the physical and chemical characteristics of the flour needs to be done. The purpose of the study was to determine the physical and chemical characteristics of Rhizophora apiculata mangrove fruit flour, as well as to test the quality of the flour. The resulted of the study showed that the physical test of Rhizophora apiculata mangrove fruit flour had a water absorption capacity of 4.26%, solubility of 1.10%, swelling power of 2.84%, and whiteness of 10.24%. The chemical test showed that flour had a water content of 12.74%, ash 2.01%, fat 1.85%, protein 2.06%, carbohydrate 81.34%, and crude fiber 11.51%. The physical characteristics of Rhizophora apiculata mangrove fruit flour can affect the mangrove fruit flour.